2020
DOI: 10.1088/1742-6596/1567/3/032079
|View full text |Cite
|
Sign up to set email alerts
|

Gamified experimental data on physics experiment to measuring the acceleration due to gravity

Abstract: This research is a first step in the model design of gamification in physics experiment that engage pre‐service physics teachers (PPTs) to an experiment system designed like gameplay. The implementation of gamification in physics experiment to measuring acceleration due to gravity (g) using the application of physical phone experiments (phyphox) on smartphone. It was involved 25 PPTs at one of the University in Bandung. This quasi-experimental research used one-group-pretest-posttest design. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…They can also try out the kit during teaching and learning sessions. The Phyphox applicationbased experimental kit developed can help teachers in their teaching, where it can engage students to understand the topic of gravitational acceleration even it is in line with the findings in [8], where Phyphox application makes practicals like games and being such experiment is more fun. The Phyphox application is more user-friendly, this free fall movement experimental kit is easy to use and can be used anywhere and anytime, this is supported by [16], where they mentioned that the Phyphox application can be carried out with equipment limited practical.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…They can also try out the kit during teaching and learning sessions. The Phyphox applicationbased experimental kit developed can help teachers in their teaching, where it can engage students to understand the topic of gravitational acceleration even it is in line with the findings in [8], where Phyphox application makes practicals like games and being such experiment is more fun. The Phyphox application is more user-friendly, this free fall movement experimental kit is easy to use and can be used anywhere and anytime, this is supported by [16], where they mentioned that the Phyphox application can be carried out with equipment limited practical.…”
Section: Resultsmentioning
confidence: 85%
“…Phyphox application used in the field of physics to retrieve and process data, in fact, it can be a good teaching tool. [8] used a gamification model to measure gravitational acceleration based on Phyphox application, where they found that students are more competitive and motivated in conducting the experiment. Meanwhile, [9] used smartphones, paper and pencil to measure the acceleration of gravity.…”
Section: Introductionmentioning
confidence: 99%
“…The apparatus was prepared by employing a smartphone as the timer when the object started to fall until it reached the lowest point of the apparatus. By using a determined distance of the falling track and the time interval noted by the smartphone, the gravity causing the object to fall could be determined with kinematic equations [27]. A similar experiment was also reported by Zhang et al which used a steel ball as the falling object [28].…”
Section: Introductionmentioning
confidence: 86%
“…Эксперимент деп түсіндірілетін белгілі бір жағдайларда зерттелетін құбылыстарды бақылау мен талдау құбылыстардың барысын бақылауға және тіркелген жағдайлар барысында оны қайталауға мүмкіндік береді [1]. Ғылыми зерттеулерде де, физиканы оқытуда да эксперимент білімнің қайнар көзі, физикалық құбылыстардың дәлелділік белгісі, логикалық және математикалық операцияларды жүргізу үшін бастапқы нүкте, теория мен тәжірибенің байланысының дәлелі болып табылады [2].…”
Section: кіріспеunclassified